2009
DOI: 10.1007/dcr.0b013e318197d0ad
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the Anus Complicating Perianal Crohn's Disease

Abstract: Physicians should have a high level of suspicion of cancer in patients with longstanding perianal Crohn's disease who have a change in symptoms. In this series, patients who were diagnosed preoperatively and treated with multimodality therapy had better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 35 publications
3
35
0
2
Order By: Relevance
“…41 Our study has also demonstrated an increased risk for cancer-related death in CD patients with FAAA. Smoking status was documented in all 6 patients undergoing surgery at our institution and in all 21 patients reported by Devon et al 12 and Gaertner et al 26 Smoking status also correlated significantly with the presence of perirectal lymph node metastases, which was the strongest predictor of poor outcome both by univariate and multivariate analysis. Although cigarette smoking has been found to be associated with an increase in colorectal cancer incidence and mortality in the general population, [42][43] it cannot be concluded definitely whether cigarette smoking independently influences the oncological outcome in CD patients with FAAA because of the low number of cases in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…41 Our study has also demonstrated an increased risk for cancer-related death in CD patients with FAAA. Smoking status was documented in all 6 patients undergoing surgery at our institution and in all 21 patients reported by Devon et al 12 and Gaertner et al 26 Smoking status also correlated significantly with the presence of perirectal lymph node metastases, which was the strongest predictor of poor outcome both by univariate and multivariate analysis. Although cigarette smoking has been found to be associated with an increase in colorectal cancer incidence and mortality in the general population, [42][43] it cannot be concluded definitely whether cigarette smoking independently influences the oncological outcome in CD patients with FAAA because of the low number of cases in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Special attention should be paid to patients with a diverted colon with a rectal stump and chronic anal fistula (Case 1 of our series and 4 cases from Devon et al 12 ), since a significantly increased cancer risk has been described in patients with a rectal remnant. 2 Furthermore, a considerable delay in diagnosis can occur because of late clinical symptoms in diverted patients.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Malignant transformation in perianal Crohn's disease is rare (adenocarcinoma is more common than squamous cell carcinoma) [79,132], but diagnosis is often delayed because of the very low sensitivity of MRI, EUS, and CT in identifying neoplastic transformation in an environment of severe chronic inflammation [78,133,134].…”
Section: Diversion Of Fecal Stream and Proctectomymentioning
confidence: 99%